2005
DOI: 10.1080/13639080500085992
|View full text |Cite
|
Sign up to set email alerts
|

Employer-university 'partnerships': a key problem for work-based learning programmes?

Abstract: This paper focuses on the development of work-based learning programmes within higher education in the UK. It explores how 'partnership' with employers came to be seen as a central aspect of this new form of provision. However, we suggest that this emphasis on partnership has been problematic. We focus, in particular, on three areas of concern. Firstly, the limited evidence that employers wish to engage in these sorts of relationships with universities. Secondly, the problems arising from the different culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…The 'academic drift' referred to by Pratt and Burgess (1974) and Pratt (1997) ' (Ibid.,38). This scepticism about the outcomes of the initiative may be well founded considering the caveats outlined in previous research into employer-university partnerships (Reeve and Gallacher 2005). However, for the Engineering Employers…”
Section: The Role Of Industrial or Employer Representative Bodies In mentioning
confidence: 99%
“…The 'academic drift' referred to by Pratt and Burgess (1974) and Pratt (1997) ' (Ibid.,38). This scepticism about the outcomes of the initiative may be well founded considering the caveats outlined in previous research into employer-university partnerships (Reeve and Gallacher 2005). However, for the Engineering Employers…”
Section: The Role Of Industrial or Employer Representative Bodies In mentioning
confidence: 99%
“…In Model C this may well not be the case, as employers are likely to need reassurance that the provision they are procuring is meeting their organisational needs, leading them to challenge academic culture and require greater precision regarding the value of course content and delivery. This could be regarded, by employers, as 'quality assurance', although again definitions of 'quality' in higher education may be quite different from an employer's understanding of quality, just as understandings of knowledge and learning may diverge (Reeve and Gallacher 2005). It is also possible that employers are reassured by the institution's cultural capital or reputation, both in terms of notions of 'quality' and in terms of the approach of employees towards the provision.…”
Section: Model C: He Programme Developed In Response To or With Indivmentioning
confidence: 99%
“…Research and evaluation has indicated the difficulties with bringing together employers and higher education institutions in partnership arrangements to develop the workforce, emphasising differences in culture and conceptions of 'knowledge' and 'learning' (Reeve and Gallacher 2005), the importance of adapting institutional processes and structural capital (Garnett et al 2008), and the challenges of engaging academic staff in activities often seen as peripheral to the core responsibilities of teaching full time students and conducting research (Eyres et al 2008, Kewin et al 2011, Timilin et al 2010. It is suggested that the roles of the institution and partnering employer need to be agreed yet remain distinct (Slotte and Tynjala 2003), although the difficulties of meeting the expectations of all stakeholders may serve to pull partnerships apart (Gustavs and Clegg 2005).…”
Section: Workforce Development Design and Delivery Processesmentioning
confidence: 99%
“…Reeve and Gallacher (2007) highlight the tensions that can be experienced when including employers in developed.…”
mentioning
confidence: 99%
“…This structure was directly influenced by employers who raised concerns with by Reeve and Gallacher (2007).…”
mentioning
confidence: 99%